Exploitable fish waste and stranded beach debris in the Emilia-Romagna Region (Italy). (August 2018) - Greggio, Nicolas; Carlini, Carlotta; Contin, Andrea; Soldano, Mariangela; Marazza, Diego
Highlights: Fish wastes and beach debris availability in the Emilia-Romagna Region is estimated. A classification method for both marine residues is proposed. 0.2 Gg/year of fish waste are located at the 5 major fish markets Region. About 63 Gg/year of sieved beach debris are collected each year in the Region. Every year 19 Gg of organic material, 8 Gg of shells and 5 Gg of stones are landfilled. Abstract: Within Circular Economy principles, this paper analyses and estimates exploitable marine residues, such as fish waste and stranded debris in beaches and their potential valorisation scenarios. The Emilia-Romagna Region (Italy) has been chosen as a case study. Based on the sold fish, about 200 Mg/year of fish waste are produced at the five major fish markets of the Region. Including all regional fish processing plants and retail trade, the estimated availability of fish waste increases up to 30, 000 Mg/year. Stranded beach debris collected by mechanical cleaning operations are currently deposited in landfill. About 63, 000 Mg/year of sieved debris are collected each year, out of which the recoverable fractions consist of 19, 000 Mg/year of organic material, 8, 000 Mg/year of shells and 5, 200 Mg/year of stones. Classification and valorisation routes for these residual biomasses are proposed and their applicability to other regions discussed. In order to investigate the possible use in anaerobic digestion plants and the effects on biogas production, Biochemical Methane Potential (BMP) assays have been carried out with fish waste samples and with organic material found in marine debris. Salt content in driftwood has been quantified to assess its potential use in Combined Heat and Power (CHP) plants. Proposed valorisation routes for shells and stones include the production of calcium carbonate (cement industry, wastewater treatment and mulching) and the application in building industry, respectively.